WHITE-TAILED EAGLE (AVES: ACCIPITERIFORMES) STATUS IN REPUBLIC OF MOLDOVA - Vitalie Ajder; Igor Roşca; Lucian Eugen Bolboacă; Laurenţiu Petrencu; Emanuel Ştefan Baltag (European Scientific Journal, ESJ, 2014)
White-tailed Eagle (Haliaeetus albicilla) is the biggest bird of prey from the Republic of Moldova which recorded a drastic decline until the 19th century. In 2001 it was mentioned only as probable breeding species in the 2nd edition of the Red Book of the Republic of Moldova. The threats of this species are unknown for our research area and the studies on White-tailed Eagle are more than 30years old. During 2012 - 2013 we have conducted a survey programme for the White-tailed Eagle in Western Republic of Moldova to search for breeding evidence or to identify suitable habitats. During our surveys we have discovered 4 breeding pairs in the riparian forests from the Prut River. All nests were recorded on poplar (Populus sp.) in areas with fish farms or big lakes. Three of them had two fledglings in 2013, which implies a good feeding area. In April 2013 we have recorded an adult bird with a territorial behaviour, near the Dniester River, but we couldn't find the nest. This is the first White-tailed Eagle survey after 1981 from the Republic of Moldova. In the next years we plan to cover the entire territory of the country in order to record all the breeding pairs of this species or to identify the suitable habitats. White-tailed Eagle is a protected species for the Republic of Moldova being listed in Annex 3 of law 439/1995 (Republic of Moldova) as endangered.